PENINGKATAN SURVIVAL RATE BENIH UDANG WINDU (Peaneus monodon) DENGAN PERENDAMAN EKSTRAK ETANOL KARAMUNTING (Melastoma malabahricum) - Awaludin Awaludin; Ridwan A (Jurnal Harpodon Borneo, 2016)
One of the causes for the decline of tiger shrimp production due to slow growth and high mortality. Many ways have been done by fish farmers in the town of Tarakan to increase the production of one of them is by antibiotics, but it is an environmentally friendly manner. The use of natural materials can be an alternative solution to accelerate growth and suppress mortality. Karamunting plant is a herbaceous plant that does not have economic value and are found in Indonesia, especially in Kalimantan, this plant contains a precursor lanosterol as shrimp growth. This research was conducted with several stages: (1). The extraction of karamunting plant (Melastoma malabathricum), (2). Treatment by dipping the extract into the tiger shrimp (Penaeus monodon) maintenance for 4 weeks variable concentrations of 0 (control), 100 ppm (P1), 75 ppm (P2), 50 ppm (P3), 20 ppm (P4) and 10 ppm ( P5), (3). Measured parameter of survival rate black tiger shrimp and (5) Data analysis. The statistical results showed that the survival rate of the ethanol extract showed significantly different Karamunting (P˂0,05). The average survival rate in the controls (43.06 ± 10.22%), P1 (78.06 ± 8.55%), P2 (75.33 ± 4.91%), P3 (66 ± 12.39% , P4 (70.66 ± 5.34%) and P5 (75 ± 4.71%). Keywords : Karamunting (Melastoma malabhatricum), Black tiger shrimp (Penaeus monodon), Survival rate.